The theoretical framework and application on the relationships between family functioning, alexithymia and emotional intelligence among early adolescents - Naghavi, Fataneh; Redzuan, Ma'rof (Marsland Press, 2012)
With respect to the relationship between family functioning, alexithymia, and early adolescent’s emotional intelligence construct is still being developed with empirical support. Hence, our the previous researches showed that how family functioning, alexithymia and several family’s characters could effect on early adolescent’s emotional intelligence. This study defines and discusses the theoretical framework in terms of the relationships between family functioning, alexithymia and several families’ factors that influence on early adolescent’s emotional intelligence, specifically.